Genomic insights into the evolution and mechanisms of carbapenem-resistant hypervirulent Klebsiella pneumoniae co-harboring bla KPC and bla NDM: implications for public health threat mitigation - Qian Wang; Yue Liu; Ran Chen; Meng Zhang; Zaifeng Si; Yueling Wang; Yan Jin; Yuanyuan Bai; Zhen Song; Xinglun Lu; Mingju Hao; Yingying Hao (BMC, 2024)
Abstract Background Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP) co-producing bla KPC and bla NDM poses a serious threat to public health. This study aimed to investigate the mechanisms underlying the resistance and virulence of CR-hvKP isolates collected from a Chinese hospital, with a focus on bla KPC and bla NDM dual-positive hvKP strains. Methods Five CR-hvKP strains were isolated from a teaching hospital in China. Antimicrobial susceptibility and plasmid stability testing, plasmid conjugation, pulsed-field gel electrophoresis, and whole-genome sequencing (WGS) were performed to examine the mechanisms of resistance and virulence. The virulence of CR-hvKP was evaluated through serum-killing assay and Galleria mellonella lethality experiments. Phylogenetic analysis based on 16 highly homologous carbapenem-resistant K. pneumoniae (CRKP) producing KPC-2 isolates from the same hospital was conducted to elucidate the potential evolutionary pathway of CRKP co-producing NDM and KPC. Results WGS revealed that five isolates individually carried three unique plasmids: an IncFIB/IncHI1B-type virulence plasmid, IncFII/IncR-type plasmid harboring KPC-2 and IncC-type plasmid harboring NDM-1. The conjugation test results indicated that the transference of KPC-2 harboring IncFII/IncR-type plasmid was unsuccessful on their own, but could be transferred by forming a hybrid plasmid with the IncC plasmid harboring NDM. Further genetic analysis confirmed that the pJNKPN26-KPC plasmid was entirely integrated into the IncC-type plasmid via the copy-in route, which was mediated by TnAs1 and IS26. Conclusion KPC-NDM-CR-hvKP likely evolved from a KPC-2-CRKP ancestor and later acquired a highly transferable bla NDM-1 plasmid. ST11-KL64 CRKP exhibited enhanced plasticity. The identification of KPC-2-NDM-1-CR-hvKP highlights the urgent need for effective preventive strategies against aggravated accumulation of resistance genes.